STUDI DESKRIPTIF TENTANG PEMANFAATAN INTERNET SEBAGAI MEDIA PEMBELAJARAN - Diana Diana (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
The aim of research to examine the use of the Internet as a medium of learning. The result shows: 1) Human resources 79.1% of the students were able to use the internet. 74.2% of respondent happy when lecturer assign tasks with internet media, but 14,2% feel anxiety. Learning resources obtained from the lecturers and the internet (55%), internet usage only media content downloading and uploading. 73.3% the students categorized as medium users. 2) Facilities on the Internet is widely used e-learning (56.7%) and web searching (39.2%). 3) infrastructure, 95.8% of students own a laptop and 93.3% have a private network for internet access. Speed internet access on campus assessed quickly and campus hotspot so that utilization is quite high. 4) Student perceptions include the perception of ease of access to the Internet, the usefulness of the Internet, the Internet influence on the process and learning outcomes in both categories.